i-Generalized Homeomorphisms and Generalized i-Homeomorphisms in Topological Spaces - Sabih W. Askandar (College of Education for Pure Sciences, 2018)
In this paper, topological ig-Homeomorphisms and topological gi-Homeomorphisms are introduced. Further, the relations between these two classes and some other classes of Homeomorphisms are investigated.